2014
DOI: 10.1073/pnas.1400138111
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of carrier dynamics in p(n)-type GaAs by scanning ultrafast electron microscopy

Abstract: Four-dimensional scanning ultrafast electron microscopy is used to investigate doping-and carrier-concentration-dependent ultrafast carrier dynamics of the in situ cleaved single-crystalline GaAs(110) substrates. We observed marked changes in the measured timeresolved secondary electrons depending on the induced alterations in the electronic structure. The enhancement of secondary electrons at positive times, when the electron pulse follows the optical pulse, is primarily due to an energy gain involving the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
83
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(88 citation statements)
references
References 18 publications
(15 reference statements)
4
83
1
Order By: Relevance
“…The nanometer escape depth of the SE probe [19,20] gives the potential to address dynamics at surfaces and interfaces of today's nano-scale devices, where many applications rely on the interplay between semiconductors and insulators. Measurements performed with USEM have shown that SE are sensitive to the excitation of electrons in semiconductors triggered by optical pulses [21][22][23], but the technique has never been applied to insulators. In this paper we report the first USEM measurement on a thin film of alumina on silicon.…”
Section: Introductionmentioning
confidence: 99%
“…The nanometer escape depth of the SE probe [19,20] gives the potential to address dynamics at surfaces and interfaces of today's nano-scale devices, where many applications rely on the interplay between semiconductors and insulators. Measurements performed with USEM have shown that SE are sensitive to the excitation of electrons in semiconductors triggered by optical pulses [21][22][23], but the technique has never been applied to insulators. In this paper we report the first USEM measurement on a thin film of alumina on silicon.…”
Section: Introductionmentioning
confidence: 99%
“…Within the family of ultrafast electron microscopy [8], scanning ultrafast electron microscopy (SUEM) [25,26] is a newly developed technique that is particularly suitable for studying photocarrier dynamics in its secondary-electrondetection mode. SUEM interfaces a conventional scanning electron microscope (SEM) with a femtosecond ultrafast laser, and operates on the principle that the local secondary electron yield is related to the local electron or hole population [27,28]. Since it is based on an SEM, SUEM can be used to characterize normal SEM samples, including bulk and microscopic samples with different structures and surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…SUEM experiences the same charging issue as the normal SEM, so in principle is not suitable to study electrically insulating materials, although the environmentalmode SUEM [29] can be a potential solution. SUEM has been utilized to image ultrafast photocarrier dynamics on the surface of a wide range of materials, including crystalline semiconductors [28,30], semiconducting nanowires [31] and nanocrystals [32], amorphous semiconductors [33], semiconductor p-n junctions [34] and two-dimensional materials [35], and these applications have resulted in intriguing observations such as ballistic transport of photocarriers across a p-n junction [34], superdiffusion of photocarriers in heavily-doped semiconductors [30] and spontaneous spatial separation of electrons and holes in amorphous semiconductors [33]. Whereas there has been an abundance of recent reviews of ultrafast electron microscopy [8,9,[36][37][38], we dedicate this article specifically to SUEM, with an emphasis on the current understanding of various physical processes that contribute to the contrast images observed in SUEM from a users' perspective.…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45][46][47][48][49][50][51][52][53][54][55] In particular, the invention of scanning ultrafast electron microscopy (S-UEM) provided the unique opportunity to selectively map charge carrier dynamics on the surface of a material with nm spatial and subpicosecond temporal resolutions. [56][57][58][59][60][61][62] In S-UEM, the optical pulse generated from a femtosecond (fs) laser system is used to generate electron packets from the tip of the scanning electron microscope, instead of the continuous electron beam used in the conventional setup. This pulse is synchronized with another optical excitation pulse that initiates carrier dynamics in the sample (Scheme 1).…”
mentioning
confidence: 99%
“…The dark contrast at negative time can be attributed to the diffusion of plasmon-excited carriers that are generated from deeper areas of the sample by electron impact, which can be perturbed by electron-hole pairs generated by the clocking photon pulse, or to different scattering processes. 58,62 At positive time delays, the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 9 optical pulse promotes a fraction of the valence-band electrons to the conduction band.…”
mentioning
confidence: 99%